2015
DOI: 10.1002/2014pa002704
|View full text |Cite
|
Sign up to set email alerts
|

Threshold behavior of a marine‐based sector of the East Antarctic Ice Sheet in response to early Pliocene ocean warming

Abstract: We investigate the stability of the East Antarctic Ice Sheet (EAIS) on the Wilkes Land continental margin, Antarctica, utilizing a high-resolution record of ice-rafted debris (IRD) mass accumulation rates (MAR) from Integrated Ocean Drilling Program Site U1359. The relationship between orbital variations in the IRD record and climate drivers was evaluated to capture changes in the dynamics of a marine-based ice sheet in response to early Pliocene warming. Three IRD MAR excursions were observed and confirmed vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 69 publications
0
30
0
Order By: Relevance
“…The IODP Site U1359 was drilled in 4,003 m water depth within 100 km of the shelf break on the Wilkes Land margin and recovered Pliocene sediments between ca 50 and 150 mbsf (Figure 1). At Site U1359, as part of this study, 110 samples were analysed across the MPWP, and merged with the previously published record of Hansen et al (2015). Pliocene sediments recovered at IODP Site U1359 consist primarily of silty clays and diatomaceous silty clays with dispersed clasts (>2 mm) with up to ca 43% biogenic silica (Hansen et al, 2015).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The IODP Site U1359 was drilled in 4,003 m water depth within 100 km of the shelf break on the Wilkes Land margin and recovered Pliocene sediments between ca 50 and 150 mbsf (Figure 1). At Site U1359, as part of this study, 110 samples were analysed across the MPWP, and merged with the previously published record of Hansen et al (2015). Pliocene sediments recovered at IODP Site U1359 consist primarily of silty clays and diatomaceous silty clays with dispersed clasts (>2 mm) with up to ca 43% biogenic silica (Hansen et al, 2015).…”
Section: Methodsmentioning
confidence: 99%
“…Here the transport history of the sand components recovered from Pliocene Antarctic drillcores is evaluated through detailed analyses of terrigenous particle‐size distributions along with scanning electron microscopy (SEM) of quartz grain microtextures. Previous work has shown that high‐resolution records of the abundance of coarse sand recovered from deep‐sea drillcores on the Wilkes Land margin indicate a response to orbital forcing in the obliquity and precession bands (Hansen et al, 2015; Patterson et al, 2014). However, the contribution of the Neogene Antarctic Ice Sheet to global ice volume changes in the precession band is debated (Caballero‐Gill et al, 2019; DeVleesschouwer et al, 2017), warranting investigation of the precise nature of the ice‐rafted sediment fluxes (Gilbert, 1990).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ma (Lisiecki & Raymo, 2005). Hansen et al (2015) also shows a shift to a dominant precession response of Wilkes Land EAIS IRD at ~4.6 Ma. Other studies of Wilkes Land EAIS marine sediment cores (Patterson et al, 2014) show a dominant periodicity of 40kyrs between 4.3 and 3.5 Ma and transition to precession thereafter.…”
Section: Orbital Forcings During the Pliocene Epochmentioning
confidence: 85%
“…During periods of smaller axial tilt, the insolation distribution anomaly decreases between winter and summer, but increases between equatorial and polar latitudes. As a result, warmer winters increase meridional moisture transport and cooler summers minimize seasonal melt back, thus increasing ice sheet surface mass balance (Raymo & Nisancioglu, 2003;Hansen et al, 2015).…”
Section: Orbital Forcings During the Pliocene Epochmentioning
confidence: 99%